Pengelolaan Partisipasi Masyarakat dalam Mendukung Program Sekolah di SMA Negeri 1 Cigugur Kabupaten Pangandaran - Hendra Hendra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
Educational institutions place the role and function of public relations (PR) as a very important part. From the perspective of educational administration, PR is a component of educational administration activities. Its realization involves activities conducted by the school in collaboration with the community. School activities related to the community are aimed at creating a harmonious partnership between the school and the community. The participation of the community with educational institutions, as a form of contribution to the advancement of these institutions, deserves managerial attention in order to provide a better and more significant contribution to the development of education, ultimately working together to achieve quality education in schools. Therefore, the purpose of this research is to understand the role of public relations management in managing community participation at SMA Negeri 1 Cigugur. This study employs a qualitative approach with a phenomenological method, using data collection techniques such as interviews, observations, open and directed discussions, and documentation studies involving the principal, teachers, the committee, and parents of students at SMA Negeri 1 Cigugur to describe the role of public relations management in enhancing community participation. The results show that the role of PR in managing community participation to support school programs at SMA Negeri 1 Cigugur, Pangandaran Regency, involves forming discussions with parents/guardians and a committee consisting of two representatives from each class of grade X. The types and forms of community participation in supporting school programs at SMA Negeri 1 Cigugur include voluntary work, participation in decision-making, contribution of ideas, and participation in funding. Supporting factors for community participation in school programs at SMA Negeri 1 Cigugur include good communication between the school and parents and the community. Another hindering factor is the limited time for parents to supervise their children's learning at home due to unavoidable work commitments.